Analisis Posisi Pembiayaan Per Sektor Ekonomi pada Perbankan Syariah di Indonesia - Aqidah Asri Suwarsi (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
The purpose of this study is to find a combination of financing portfolio that produces the smallest financing risk based on investor preference and based on the amount of financing in the economic sector at Sharia Commercial Bank. The research method is analytical descriptive research using secondary data obtained from a publication of Bank Indonesia (Statistik Perbankan Syariah) covering monthly data of financing position of 10 (ten) economic sector during January 2011-March 2014 for BUS / UUS category. Analyzer used by Markowitz Method. The results obtained from the research show BUS / UUS in Indonesia there is a combination of different economic sectors in the distribution of financing with the smallest financing risk. Optimal portfolio of financing distribution based on BUS risk preference to economic sector can be obtained if BUS distributes to Economic Sector of Business Services, then Transportation, Warehousing and Communication sector, then Construct. The smallest optimal risk portfolio of financing disbursements based on economic sector in Indonesia focuses on the business sector of the business economy, then the social services sector, then the mining sector.Keywords: Sharia Bank Financing, Economic Sector Financing, Optimal Portfolio, Shariah Bank Preferences Minimum Funding Risk, Markowitz Method